Variabel â Variabel Yang Dapat Memengaruhi Peringkat Obligasi (Studi Kasus Perusahaan Non Keuangan dan Non Jasa yang Terdaftar di Bursa Efek Indonesia) - Tensia, Kurnia Oktavianti; Yaya, Rizal; Supriyono, Edi (Jurnal Bisnis Teori & Implementasi)
In this thesis, the author examines the variables that can affect the bond ratings issued by rating agency PT. PEFINDO on non-financial companies and non-services that are listed in the Indonesia Stock Exchange. Variables that are used to influence bond ratings that leverage ratio, liquidity ratio, profitability, productivity ratio, firm size, maturity and independent commissioners.The samples used were 116 with conventional bonds, to publish financial statements, have complete data, have positive earnings and bonds with AAA-BBB ratings during the observation period 2004 to 2013. Testing the hypothesis in this study using logistic regression.The results showed there are several variables that can affect the bond ratings and there are several variables that do not affect the bond ratings. Variables that can affect the bond ratings of variable leverage ratios, profitability ratios, company size, maturity, and independent commissioner. Meanwhile, the variables that do not affect the bond ratings of variable liquidity ratio and the productivity ratio.